A critical assessment of the abuse, dependence and associated safety risks of naturally occurring and synthetic cannabinoids - Heal, David J.; Gosden, Jane; Smith, Sharon L. (Frontiers in Psychiatry, 2024)
Various countries and US States have legalized cannabis, and the use of the psychoactive 1 and non-psychoactive cannabinoids is steadily increasing. In this review, we have collated evidence from published non-clinical and clinical sources to evaluate the abuse, dependence and associated safety risks of the individual cannabinoids present in cannabis. As context, we also evaluated various synthetic cannabinoids. The evidence shows that delta-9 tetrahydrocannabinol (Δ 9 -THC) and other psychoactive cannabinoids in cannabis have moderate reinforcing effects. Although they rapidly induce pharmacological tolerance, the withdrawal syndrome produced by the psychoactive cannabinoids in cannabis is of moderate severity and lasts from 2 to 6 days. The evidence overwhelmingly shows that non-psychoactive cannabinoids do not produce intoxicating, cognitive or rewarding properties in humans. There has been much speculation whether cannabidiol (CBD) influences the psychoactive and potentially harmful effects of Δ 9 -THC. Although most non-clinical and clinical investigations have shown that CBD does not attenuate the CNS effects of Δ 9 -THC or synthetic psychoactive cannabinoids, there is sufficient uncertainty to warrant further research. Based on the analysis, our assessment is cannabis has moderate levels of abuse and dependence risk. While the risks and harms are substantially lower than those posed by many illegal and legal substances of abuse, including tobacco and alcohol, they are far from negligible. In contrast, potent synthetic cannabinoid (CB1/CB2) receptor agonists are more reinforcing and highly intoxicating and pose a substantial risk for abuse and harm. 1 "Psychoactive" is defined as a substance that when taken or administered affects mental processes, e.g., perception, consciousness, cognition or mood and emotions.